The Bun gun - Strong, Jeremy; Cunliffe, Ian, illus (London : Puffin, 2004)
The Children at Pirate School are fed up. Patagonia Clatterbottom, their head teacher, has a big cupboard full of yummy food, but it's all locked up. Even worse-other pirates are planning to steal the food. Luckily, the children have a secret weapon...
Keywords: Pirates; School story